Rhetorical moves and metadiscourse used in abstracts of ESL engineering undergraduates' term papers in a Malaysia public university - Chuah, Ek Lon (2015)
The abstract functions to provide a quick overview of a research report or an article. It is usually the last item written by authors after they have completed the main sections in the report. Readers usually will decide whether to read further or reject the article after the first reading of the abstract. Therefore, an abstract should be clear and concise to ‘sell’ their research to the readers or to reviewers to select participation in conferences. Given the importance of an abstract, it is essential for writers, especially novice writers like undergraduate writers to know the appropriate writing conventions and use them appropriately in academic writing to engage the readers. Numerous studies have focused on research article abstracts. However, focus on final term paper abstracts of undergraduates is still scarce. This study investigated the rhetorical move patterns in the abstracts of undergraduates’ final term papers in the engineering discipline from a Malaysian public university. In congruence with the move patterns, this study also investigated the metadiscourse features that help to signal the moves and perform a social and linguistic function. In analyzing the move patterns, Pho’s (2008) model of abstract analysis was used, while metadiscourse analysis was governed by Hyland’s (2005) framework. A concordancer MP2.2 was used to determine the frequency of metadiscourse use in the abstracts. This study also embarked on the investigation of possible combinations of the move patterns. As far as move patterns were concerned, Move 1- Situating the research, Move 2-Presenting the research and Move 3- Describing the methodologywere the obligatory moves while Move 4- Summarizing the findings and Move 5- Discussing the research were optional moves. The results were somewhat in contrast with the past studies on abstracts where Move 2-Presenting the research, Move 3- Describing the methodology and Move 4-Summarizing the findings were te obligatory moves. The most frequent combination of the moves wereMove 1, Move 2 and Move 3. As for metadiscourse, this study found that interactive forms was found to be higher than interactional forms. The highest category of interactive form was transition markers, while interactional form was engagement markers. In many past studies on metadiscourse,transition markers was also found to be highly used. The results will have a bearing on pedagogical implications and will also inform students of related genre expectations towards abstract writing. This qualitative and quantitative study would give insights to teachers to help students to craft an effective abstract to engage readers. However, this study focused only on a single discipline of undergraduates’ final term papers. Future investigation on rhetorical move patterns and metadiscourse in abstracts could be extended to different disciplines and categories of students, such as postgraduates. Studies can also be carried out to compare abstracts written by students who are proficient and not proficient to identify differences in the use and combination of move patterns as well as the metadiscourse involved.